2018
DOI: 10.1155/2018/1070151
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Levels at the Midpregnancy Can Predict Gestational Complications

Abstract: Although essential for a successful pregnancy, a growing body of evidence suggests that maternal inflammation, when dysregulated, may represent a risk factor for both maternal and neonatal outcomes. Here, we assessed the accuracy of maternal C-reactive protein (CRP) concentrations at the middle phase of pregnancy in the identification of maternal adverse outcomes (MAO) until delivery. A correlation between CRP and a complicated pregnancy including both maternal and neonatal adverse outcomes has been investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
1
22
0
2
Order By: Relevance
“…Additionally, chronic low‐grade inflammation in adipose tissue impairs insulin signaling, which further stimulates expression of genes encoding proteins involved in insulin resistance. In this study, significant change of C‐reactive protein in 16‐18 gestational weeks may verify its role as early pregnancy predictor for developing GDM 28,29 and co‐regulations of this protein with proteins in inflammation and membrane proteins may indicate the way it works.…”
Section: Discussionmentioning
confidence: 78%
“…Additionally, chronic low‐grade inflammation in adipose tissue impairs insulin signaling, which further stimulates expression of genes encoding proteins involved in insulin resistance. In this study, significant change of C‐reactive protein in 16‐18 gestational weeks may verify its role as early pregnancy predictor for developing GDM 28,29 and co‐regulations of this protein with proteins in inflammation and membrane proteins may indicate the way it works.…”
Section: Discussionmentioning
confidence: 78%
“…Other analyses have found elevated CRP among pregnant women who deliver preterm 24,47‐50 . There is a growing literature supporting a role for harmful social and structural factors in the association between African American race and preterm birth 50‐52 .…”
Section: Discussionmentioning
confidence: 99%
“…Study Population and Clinical Assessment. As previously described [3], 380 consecutive outpatient pregnant women between the 24 th and 26 th gestational week (gestational age 23 weeks + 0 days-25 weeks + 6 days) aged 18 or older attending the Diabetology Unit of IRCCS Ospedale Policlinico San Martino (Genoa, Italy) were enrolled from October 2012 to November 2014. No other specific inclusion criteria than a pregnant status were established, while exclusion criteria consisted in clinical suspicion of an active infection or concurrent treatment with corticosteroids (n = 9), thus leaving 371 patients eligible for analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in approximately 1-6% of healthy women, the presence of high levels of APL autoantibodies can be detected and can potentially affect physiological pregnancy [1,2]. As well, we recently found that even moderately high levels of C-reactive protein (CRP), a classical biomarker of systemic inflammation, can help in recognizing pregnant women at increased risk for adverse outcomes [3], thus highlighting the pivotal effect that inflammation may have during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation